Effects of injection pressure, exhaust gas recirculation and intake pressure on the cycle-to-cycle variations of HCCI combustion. Issue 2 (May 2016) - You-cheng, Sun; Min, Xu; Yong, Gui; Yi, Cui; Lei, Shi; Kang-yao, Deng
Abstract: Combustion in HCCI engines is a controlled auto ignition process of well-mixed fuel, air and residual gas. Since the ignition of HCCI combustion is completely controlled by chemical kinetics, and is directly affected by the fuel composition, equivalence ratio, and thermodynamic state of the mixture, there is no direct control on the start of combustion process. Therefore, HCCI combustion is easy to become unstable, especially at lower and higher engine loads. In this study, cycle-to-cycle variations of an HCCI combustion engine fuelled with diesel were investigated on a modified single-cylinder engine. The experiments were conducted at different injection pressures, EGR rates, and intake pressures at constant engine speed of 1500 rpm. One hundred consecutive combustion cycles for each test conditions at steady state operation were recorded. Consequently, cycle-to-cycle variations of the main combustion parameters and performance parameters were analyzed. Coefficients of variation (COV) of every parameter were calculated to evaluate the cycle-to-cycle variations of HCCI combustion. This provides basis for closed loop control of diesel HCCI combustion phasing.